2016
DOI: 10.1039/c6cp02981g
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of short DNA helices under mechanical stretching

Abstract: The flexibility of short DNA fragments is studied by a Hamiltonian model which treats the inter-strand and intra-strand forces at the level of the base pair. The elastic response of a set of homogeneous helices to externally applied forces is obtained by computing the average bending angles between adjacent base pairs along the molecular axis. The ensemble averages are performed over a room temperature equilibrium distribution of base pair separations and bending fluctuations. The analysis of the end-to-end di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 101 publications
(129 reference statements)
1
16
0
Order By: Relevance
“…The method followed here is similar in spirit to the procedure reported in different earlier publications. [6,9,10,12,21,[47][48][49][50][51][52]].…”
Section: Calculation Of the Persistence Length (L P )mentioning
confidence: 99%
“…The method followed here is similar in spirit to the procedure reported in different earlier publications. [6,9,10,12,21,[47][48][49][50][51][52]].…”
Section: Calculation Of the Persistence Length (L P )mentioning
confidence: 99%
“…To address these issues we have recently applied a mesoscopic Hamiltonian model, which treats the dsDNA at the level of the base pair [26,27], to the analysis of the looping probabilities in short molecules: the obtained J-factors fit the order of magnitude of the experimental data and reproduce the observed trend as a function of the fragment size [28]. Importantly, radial fluctuations between the pair mates and large bending angles between adjacent base pairs have been incorporated in the computational method thus allowing for the formation of kinks which locally unstack the helix [29][30][31][32], enhance the cyclization efficiency and may reduce the persistence length [23,[33][34][35].…”
Section: Analysis Of Looping Probability Induced By T4 Ligase Enzymesmentioning
confidence: 99%
“…This has also been suggested more recently by molecular dynamics simulations [78] and analysis of (un)looping probabilities in short chains based on single molecule fluorescence resonance energy transfer [79]. While the polymer flexibility can be directly related to the average bending angles between any two distant monomers [80,81], computation of persistence length has shown that linear short sequences have an intrinsic flexibility mainly ascribed to their terminal base pairs [42,82].…”
Section: Methodsmentioning
confidence: 86%